Relational Goes Beyond Interpersonal: The Development of Empathy in the Context of Culture. (October 2020) - Main, Alexandra; Kho, Carmen
It is clear a relational approach to the study of empathy is gaining traction across multiple disciplines. Both commentaries on "A Relational Framework for Integrating the Study of Empathy in Children and Adults" underscored the need to expand the relational framework of empathy to incorporate the broader social and cultural context in which children and adults live. In the present reply we outline some specific ways that culture can inform the study of empathy in interpersonal contexts. We focus on how culture and context shape the meaning of empathy and its expression and highlight how a within-culture approach to the study of empathy will advance our understanding of this nebulous construct.